Pengaruh Bank-spesific Factors dan Kondisi Ekonomi terhadap Kinerja Maqashid Syariah BUS di Indonesia - Fitri Syahbani Rozak; Fatmi Hadiani; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2021)
Islamic banking is a financial institution based on Sharia principles. Therefore, a measurement of the performance of Islamic banking needs to be distinguished from the measurement of the performance of conventional banking. This performance is not only the performance in generating profits, but rather the performance of Islamic banks in meeting social benefits. This performance can be measured by the maqashid sharia index. The policies of each bank are different because the internal conditions of a bank are not the same and each bank also faces different macroeconomic conditions every year. This study aims to determine the effect of bank-specific factors represented by bank size and CAR and macroeconomic conditions represented by GDP, inflation and exchange rates on the Islamic maqashid index. The object of this research is Islamic Commercial Banks in Indonesia which consistently operate as BUS during the period 2014 to 2018. The type of data used is secondary data obtained from the annual reports of each BUS, BPS statistical data and BI statistics. This research method uses descriptive quantitative with panel data regression analysis techniques. The results of this study indicate that bank size, inflation and exchange rates, do not have a significant effect on the performance of Islamic Maqashid. Meanwhile, the CAR and GDP have a significant negative and positive effect on the performance of Maqashid Syariah.